Association between insufficient medication of antihypertensives and the severity of acute ischemic stroke. Issue 1 (December 2015) - Lee, Kyung; Lee, Jeong-Yoon; Choi, Nari; Yoon, Jee-Eun; Shin, Dong-Won; Kim, Ji-Sun; Roh, Hakjae; Ahn, Moo-Young; Hwang, Hye-Won; Hyon, Min-Su
Abstract Background Although recent studies have suggested that adherence to antihypertensive treatment reduced stroke incidence, the relationship of adherence to antihypertensives with stroke severity has not been studied. This study attempted to know whether nonadherence before stroke is associated with initial severity of acute ischemic stroke. Methods Consecutive patients with acute ischemic stroke were identified in Soonchunhyang University Hospital from Mar 2005 to Aug 2014, excluding the cases without hypertension or information of antihypertensive adherence. We compared the mean of National Institute of Health Stroke Scale (NIHSS) score between adherence groups and insufficient medication group, and additionally in each stroke subtype. Multiple linear regression model was established for initial NIHSS score adjusting alleged factors linked to stroke severity. Results Initial NIHSS score were higher in insufficient medication group than adherence group (6.5 ± 7.2VS 5.4 ± 5.7, P = .11). In large artery atherosclerosis (LAA) and small vessel occlusion (SVO), initial NIHSS score were significantly higher in insufficient medication group (6.1 ± 6.5VS 4.4 ± 4.4, P = .004 for LAA; 3.8 ± 3.5VS 2.7 ± 1.8, P = .014 for SVO). In multiple linear regression model, insufficient medication to antihypertensives had a significant effect on NIHSS score (t = 3.417, P = .001) after adjusting covariates. Conclusion Insufficient medication of antihypertensives before stroke was independently associated with the severity of acute ischemic stroke. Further studies with prospective designs are warranted to evaluate clinical implication of adherence to antihypertensives for ischemic stroke.